Tomato (Solanum lycopersicum L.) grown under greenhouse conditions: correlations among variables - Monge-Pérez, Jose Eladio (2019)
For 63 tomato genotypes grown under greenhouse conditions the researchers estimated Pearson correlations among seven quantitative variables:  number of days to the start of harvest (days after transplant), fruit weight (g), number of fruits per cluster, yield (ton/ha), fruit firmness (N), percentage of total soluble solids (°Brix), and fruit juice pH.  The only two Pearson correlations evaluated in the 63 genotypes that were high (r ≥ 0,69) and statistically significant (p ≤ 0,05), were obtained among percentage of total soluble solids and fruit weight (r = -0,72), showing a linear regression statistic (R2) of 0.52; and among percentage of total soluble solids and the number of days to the start of harvest (r = -0,71; R2 = 0,50);.  Statistically significant correlations were observed in ten additional cases, not across all genotypes but estimated according the type of tomato or the planting date.